Studio de Dança Larissa Oli: o desenvolvimento psicomotor e a lucidade nas aulas de baby class - OLIVEIRA, Larissa de Paula Barros de (2022)
This paper aims to analyze descriptively and argumentatively the appreciation of children's experiences through activities specific to children's culture, such as playful and imaginative activities as one of the conducive ways for motivation in classical ballet classes. The psychomotor aspects applied in the baby class classes as an integral part of the dance teaching process, are outlined as another way in the construction of expressive senses. The method used was qualitative study, action and exploratory research, in addition to classroom experiences. (As well as bibliographic research) characterized as descriptive bibliographic research, aiming to give theoretical support to this work. Concluding with the arguments and theories presented in which psychomotricity and playfulness in the class of baby class, are fundamental elements to be worked on in Classical Ballet classes. Considering that the construction of knowledge, based on the work with the ludic, encourages children to participate in the proposed activities, as well as to elaborate goals, perceive, create and explore different stimuli, anticipating results, raising hypotheses and formulating strategies. , aiming at possible solutions to the problems.